Analyzing perspectives: A comparative study of pathologists’ and surgeons’ approaches to leftover human biological samples for research purposes – A prospective interventional study - Kurubara Amaresh; M. S. Ganachari; Revanasiddappa Devarinti (BLDE University Journal of Health Sciences)
BACKGROUND OBJECTIVE: Biological samples like blood and tissues are crucial for diagnosing, treating diseases, and research worldwide. Leftover tissues from the surgeries are known as human surplus bio specimens, these specimens are essential for biomedical research. These samples are stored by using following methods in global bio banking standards. Thus, study aimed to explore the Knowledge, Attitude, and Practice (KAP) among pathologists and surgeons on utilization of leftover samples in future research use. METHODOLOGY: A Prospective Interventional pre-and-post study targeted Participants completed self-prepared questionnaires for baseline data, underwent education using a tool, and were surveyed again after one month using the same validated questionnaires. RESULTS: Among 50 participants, majority (74%) were surgeons, with 50% having 1-5 years of professional experience. Pre and post-test analysis revealed significant improvements with mean differences in KAP scores i.e., 8.5, 12.98 and 6.46 respectively. CONCLUSION: In conclusion, the positive impact of the intervention on the KAP levels of surgeons and pathologists reflects the effectiveness of targeted interventions in enhancing awareness, understanding, and ethical practices, the study findings underscore the need for global guidelines to navigate complexities in consent procedures and make informed decisions regarding leftover samples.